The third industrial revolution in global business - Dosi, Giovanni, 1953-; Galambos, Louis (Cambridge : Cambridge University Press, 2013)
'The essays in this volume probe the impact the digital revolution has had, or sometimes failed to have, on global business. Has digital technology, the authors ask, led to structural changes and greater efficiency and innovation? While most of the essays support the idea that the information age has increased productivity in global business, the evidence of a'revolution' in the ways industries are organized is somewhat more blurred, with both significant discontinuities and features which persist from the'second' industrial revolution. Chapter One Technological Revolutions and the Evolution of Industrial Structures. Assessing the Impact of New Technologies upon the Size, Pattern of Growth and Boundaries of Firms Giovanni Dosi, Alfonso Gambardella, Marco Grazzi, Luigi Orsenigo Introduction There is little doubt that over the last three decades the world economy has witnessed the emergence of a cluster of new technologies - that is a new broad techno-economic paradigm in the sense of Freeman and Perez (1988) - centered on electronic-based information and communication technologies. Such ICT technologies did not only give rise to new industries but, even more importantly, deeply transformed incumbent industries (and for that matter also service activities), their organizational patterns, and their drivers of competitive success'--
Includes bibliographical references and index.
Keywords: Internet -- Social aspects; Information technology -- Social aspects; Industrial revolution